2013
DOI: 10.2486/indhealth.2012-0051
|View full text |Cite
|
Sign up to set email alerts
|

Mould Sensitisation among Bakers and Farmers with Work-related Respiratory Symptoms

Abstract: Fungi belong to common allergens, which can be found both in occupational and non-occupational environment. The aim of the study was to determine the frequency and factors associated with mould allergy among bakers and farmers reporting work-related respiratory symptoms. The study group comprised 117 bakers and 83 farmers reporting work-related respiratory symptoms. Skin prick tests (SPT) with common, fungal and occupational allergens, estimation of serum total IgE level, spirometry, histamine test and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
5
1
3
Order By: Relevance
“…Grouping the fungi-sensitised individuals according to the pattern of SPT reactivity showed that the largest subgroup of fungi-sensitised individuals was reactive to multiple fungi species which could have been either due to genuine sensitisation to a variety of fungi, or due to cross-reactivity between fungal allergens. Our high rate of SPT reactivity is in contrast to rates reported by other countries, ranging from 3% to 58% ( D'Amato et al., 1997 ; Arbes et al., 2005 ; Bousquet et al., 2007 ; Wiszniewska et al., 2013 ; Fernández-Soto et al., 2018 ; Kwizera et al., 2019 ). These results highlight differences between different populations and thus emphasize the need for studies to characterise sensitisation patterns in different regions of the world ( Eriksson and Holmen, 1996 ; Mpairwe et al., 2008 ).…”
Section: Discussioncontrasting
confidence: 89%
“…Grouping the fungi-sensitised individuals according to the pattern of SPT reactivity showed that the largest subgroup of fungi-sensitised individuals was reactive to multiple fungi species which could have been either due to genuine sensitisation to a variety of fungi, or due to cross-reactivity between fungal allergens. Our high rate of SPT reactivity is in contrast to rates reported by other countries, ranging from 3% to 58% ( D'Amato et al., 1997 ; Arbes et al., 2005 ; Bousquet et al., 2007 ; Wiszniewska et al., 2013 ; Fernández-Soto et al., 2018 ; Kwizera et al., 2019 ). These results highlight differences between different populations and thus emphasize the need for studies to characterise sensitisation patterns in different regions of the world ( Eriksson and Holmen, 1996 ; Mpairwe et al., 2008 ).…”
Section: Discussioncontrasting
confidence: 89%
“… 26 Exposure to mold allergens in the sensitized patients may exacerbate asthma symptoms by promoting airway inflammation, airflow limitation, and AHR. 32 33 34 A recent study in Korea has shown that sensitization to aeroallergens induce the development of AHR, but not through airway eosinophilic inflammation in mold-sensitized adult asthmatics. 14 In the present study, the findings that eosinophilic inflammatory markers in the mold-sensitized subjects were not different from the other aeroallergen-sensitized subjects, could explain that another pathway rather than eosinophilic inflammation induce airflow limitation and AHR in mold-sensitized asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the prevalence of sensitization in atopic patients varies depending on many factors as it was exemplified in several large studies. 45 , 46 , 47 , 48 , 49 A multicenter study in 7 European countries investigated the prevalence of Alternaria and Cladosporium sensitization in 877 children and adults (5-60 years) with rhinits and/or asthma. From these, approximately 9.5% were skin prick positive to at least one or both fungal species.…”
Section: Introductionmentioning
confidence: 99%